TARGET THERAPY FOR DISSEMINATED CANCER OF THE CERVIX UTERI - V. A. Gorbunova; A. v Odintsova; S. V. Khokhlova (ABV-press, 2014)
The paper gives recent data on the use of target agents, such as erlotinib, gefitinib, cetuximab, bevacizumab, and sorafinib in advanced cancer of the cervix uteri (CCI). Approaches using target drugs in combination with chemotherapy are of the greatest interest. A spec- trum of molecular biomarkers (epidermal and vascular growth factors) in CCI and its correlation with prognosis and treatment response are shown. A number of adverse relations caused by target agents are considered.